2017
DOI: 10.1097/mpa.0000000000000784
|View full text |Cite
|
Sign up to set email alerts
|

The More the Better—Lower Rate of Stage Migration and Better Survival in Patients With Retrieval of 20 or More Regional Lymph Nodes in Pancreatic Cancer

Abstract: This population-based propensity score-adjusted investigation demonstrated that more retrieved RLNs in pancreatic cancer decreases the rate of stage migration and improves the oncological outcome in node-negative and positive cancer. Contradictory results may be explained by a bias in the cancer characteristics for a different extent of RLN retrieval.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 46 publications
2
24
1
Order By: Relevance
“…While the above‐mentioned studies clearly demonstrate the importance of lymphadenectomy for prognostic staging, direct evidence on a therapeutic effect of lymphadenectomy in pancreatic cancer remains limited. An analysis of the SEER database including 7685 patients with stage I and II pancreatic cancer found that retrieval of 20 or more regional lymph nodes was associated with increased survival in node‐negative as well as node‐positive cancers after adjustment for other prognostic factors . While the improved survival with ≥20 retrieved lymph nodes in node‐negative cancers may be explained by effects of stage migration, the improved survival with ≥20 retrieved nodes in node‐positive cancers points to a possible therapeutic effect of radical lymphadenectomy .…”
Section: Extent Of Lymphadenectomy and Outcome In Pancreatic Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…While the above‐mentioned studies clearly demonstrate the importance of lymphadenectomy for prognostic staging, direct evidence on a therapeutic effect of lymphadenectomy in pancreatic cancer remains limited. An analysis of the SEER database including 7685 patients with stage I and II pancreatic cancer found that retrieval of 20 or more regional lymph nodes was associated with increased survival in node‐negative as well as node‐positive cancers after adjustment for other prognostic factors . While the improved survival with ≥20 retrieved lymph nodes in node‐negative cancers may be explained by effects of stage migration, the improved survival with ≥20 retrieved nodes in node‐positive cancers points to a possible therapeutic effect of radical lymphadenectomy .…”
Section: Extent Of Lymphadenectomy and Outcome In Pancreatic Cancermentioning
confidence: 99%
“…An analysis of the SEER database including 7685 patients with stage I and II pancreatic cancer found that retrieval of 20 or more regional lymph nodes was associated with increased survival in node‐negative as well as node‐positive cancers after adjustment for other prognostic factors . While the improved survival with ≥20 retrieved lymph nodes in node‐negative cancers may be explained by effects of stage migration, the improved survival with ≥20 retrieved nodes in node‐positive cancers points to a possible therapeutic effect of radical lymphadenectomy . In contrast to overall survival, the extent of lymphadenectomy may more directly affect local recurrence and recurrence‐free survival.…”
Section: Extent Of Lymphadenectomy and Outcome In Pancreatic Cancermentioning
confidence: 99%
“…A higher ELN count was reportedly associated with a higher PLN count and a decreased risk of false downstaging of the N classification. [ 10 ] Previous evidence has suggested that LNR, which accounts for both the PLN and ELN counts, exhibits prognostic superiority to PLN. [ 17 – 19 ] In this population-based study, we demonstrated significant prognostic heterogeneity within the 8th AJCC N1 and N2 disease after stratified by the rN classification, which verifies the prognostic value of LNR and suggests a room for improvement in the 8th AJCC staging scheme.…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 ] In addition, the total examined lymph node (ELN) count is considered to be of great importance to staging accuracy for pancreatic cancer; that is, an increased number of ELNs is reported to decrease the possibility of stage migration and improves the oncological outcome. [ 10 ] Although the recently launched 8th edition of the AJCC staging scheme for PDAC further divided the N1 classification of the 7th edition into N1 (1–3 PLNs) and N2 (≥4 PLNs), it still did not account for the impact of the ELN on prognostic accuracy. [ 11 ]…”
Section: Introductionmentioning
confidence: 99%
“…Nodal status is a potent prognostic factor 6 - 9 . Ignoring total number of examined lymph nodes (eNs), pNs perform well when the number of eNs is more than 20 10 , 11 . Besides, 15 eNs are needed to ensure node-negative status of PDAC 12 .…”
Section: Introductionmentioning
confidence: 99%